STRATEGIES FOR IMPROVING THE COMPETENCIES OF ARABIC LANGUAGE TEACHERS AT MADRASAH TSANAWIYAH AN-NIZHAM JAMBI - Shafira Albiah; Mar'atun Sholiha; M. Rohiq; Ady Muh. Zainul Mustopa (Yayasan Adra Karima Hubbi, 2026)
This research was motivated by the low competencies of Arabic language teachers at Madrasah Tsanawiyah An-Nizham Jambi, which included pedagogical, professional, social, and personality aspects. The problems identified included the use of conventional learning methods, an imbalance in mastery of Arabic language skills, limited availability of professional training, weak collaboration among teachers, and the absence of a systematic, sustainable competency development program. This research aimed to describe the implementation of strategies to improve the competencies of Arabic language teachers and to analyze their effectiveness at Madrasah Tsanawiyah An-Nizham Jambi. The research method used was a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research subjects consisted of the madrasah principal, the vice principal for curriculum affairs, Arabic language teachers, and students. Data analysis was conducted using the Miles and Huberman model, which included data reduction, data display, and conclusion drawing, and the validity was tested through triangulation. The results of the research showed that strategies for improving teacher competencies were implemented through various programs, such as training and workshops, academic supervision, participation in the Subject Teacher Forum (MGMP), the use of learning technology, and continuous professional development. However, the implementation had not been optimal due to limited resources, low training frequency, and the lack of structured, sustainable programs. However, the implemented strategies positively impacted the quality of learning, particularly through variation in teaching methods and teachers’ professional awareness. This research concludes that the strategies for improving the competencies of Arabic language teachers at Madrasah Tsanawiyah An-Nizham Jambi have been implemented fairly well but have not yet reached an optimal level. Strengthening more systematic and sustainable programs, supported by adequate policies and resources, is necessary to ensure that improvements in teacher competencies are carried out optimally.